Postcataract Surgery Endophthalmitis after Introduction of the ESCRS Protocol: A 5-year Study. Issue 4 (July 2014) - Beselga, Diana; Campos, António; Castro, Miguel; Fernandes, Cristina; Carvalheira, Fausto; Campos, Sónia; Mendes, Sílvia; Neves, Arminda; Campos, Joana; Violante, Luís; Sousa, João C.
Purpose: To present the results of a retrospective comparative unicentric institutional study of the incidence of postcataract surgery endophthalmitis before and after the introduction of the European Society of Cataract and Refractive Surgeons (ESCRS) protocol in 2007 in our department. Methods: This study included 15, 689 eyes of patients undergoing cataract surgery between 2005 and 2011. Surgeries were performed by 9 different surgeons. After June 2007, the ESCRS protocol was introduced, and all patients underwent intracameral injection of 1 mg of cefuroxime (10 mg/mL) at the end of cataract surgery. Cefuroxime was prepared prior to surgery in the operating room. All patients were observed between 6 weeks and 3 months after surgery. Results: Between January 2005 and June 2007, before the introduction of the ESCRS protocol in our department, 2299 patients underwent cataract surgery and there were 6 cases of postoperative endophthalmitis (0.26%). After the introduction of the protocol, 13, 390 surgeries were performed and there were no cases of endophthalmitis. Conclusions: Postoperative endophthalmitis is one of the most devastating cataract surgery complications. Our results provide strong evidence of the utility of cefuroxime as prophylaxis of endophthalmitis after cataract surgery.